On fatigue life variability in bone cement. Issue 15 (12th October 2020) - Schönning, Alexandra; Neal, Jonathan; Eason, Paul D.; Tiryakioğlu, Murat; Logan, Zachariah S.
Abstract : Fatigue life of Simplex P bone cement was tested at three different stress amplitudes by using specimens produced by two different mixers. Fatigue life data showed high variability in all instances. Statistical analysis showed that fatigue life was not affected by the type of mixer. Analysis of fracture surfaces showed that fatigue life variability could be attributed to the presence of defects, such as bubbles and mixing defects. Both Weibull and Tiryakioğlu distributions provided excellent fits to the fatigue life data. Moreover, the Gumbel parameters for fatigue initiator size data estimated in the Tiryakioğlu distribution agreed closely with fractographic measurements.